Dementia diagnosis disparities by race and ethnicity: Health services research: Cost of care and implications for intervention. (7th December 2020) - Lin, Pei‐Jung; Daly, Allan; Olchanski, Natalia; Cohen, Joshua T; Neumann, Peter J; Faul, Jessica D; Fillit, Howard M; Freund, Karen M
Abstract: Background: Dementia is often underdiagnosed, and self‐reported data suggest that this problem may be more common among racial and ethnic minority groups. This study examined racial and ethnic disparities in the timeliness in which individuals receive a formal dementia diagnosis. Method: This analysis used eight waves of US national surveys from 2000‐2014 Health and Retirement Study, linked with Medicare and Medicaid claims. We identified study participants age ≥70 with dementia using a well‐validated statistical model based on individual's age, gender, education, cognition, and functional limitations. We assessed the proportion of patients not receiving a coded diagnosis of dementia in their claims by the time the prediction model classified them as having dementia. We used logistic regression models to compare the likelihood of missed or delayed dementia diagnoses in claims by race and ethnicity, adjusting for patient characteristics. We analyzed dementia severity, measured by cognition (TICS scores for self‐respondents; IQCODE scores for proxy‐respondents) and functional limitations, at the time of a dementia diagnosis documented in claims, by race/ethnicity. All analyses adjusted for sampling weights. Result: Our sample included 3, 966 older adults with dementia. Forty‐two percent had a missed or delayed dementia diagnosis in their claims. This proportion was higher among non‐Hispanic blacks and Hispanics than among non‐Hispanic whites (46% and 54% vs. 41%, p<0.001). Logistic regression model indicated more frequent missed/delayed dementia diagnoses among non‐Hispanic blacks (OR=1.27; 95% CI: 1.05‐1.53) and Hispanics (OR=1.83; 95% CI: 1.43‐2.35), compared to non‐Hispanic whites. Over the study period, 76% had a dementia diagnosis documented in their claims. At the time of diagnosis, non‐Hispanic blacks and Hispanics had poorer cognitive function and more functional impairments, compared to non‐Hispanic whites. Conclusion: Non‐Hispanic blacks and Hispanics may experience missed or delayed diagnoses of dementia more often than non‐Hispanic whites. When they are diagnosed, non‐Hispanic blacks and Hispanics may have more advanced dementia compared to non‐Hispanic whites. Public health efforts such as the Brain Health Initiative should tailor campaigns to different ethnoracial groups when promoting early diagnosis of dementia. The medical community should implement provider training on culturally competent dementia care and improve documentation of dementia diagnostic findings in health insurance claims.